2016
DOI: 10.24966/he-9640/100002
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Peroxidase and Thyroglobulin Antibodies and Ophthalmopathy in Patients with Graves’ Disease, Hashimoto Thyroiditis and Transient Thyroiditis

Abstract: ConclusionOverall, we have not shown any significant relationship between negative TPO or TG antibody tests, or low serum titres of either antibody, and eye signs, in patients with GD, Hashimoto thyroiditis or transient thyroiditis. TPO and TG antibodies are thus unlikely to play a major role in the pathogenesis of GO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…This model included several risk factors and showed that subjects who had elevated Anti-TG values had a 21-times-higher probability of developing IOP elevation. Thyroglobulin (Tg) has been proposed to play a role in GO [ 34 , 35 , 36 ]. Polymorphisms in Tg, along with a combination of iodine and the enzymatic activity of thyroid peroxidase required for thyroid hormone synthesis, may unintentionally trigger an autoimmune response in the thyroid [ 36 , 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This model included several risk factors and showed that subjects who had elevated Anti-TG values had a 21-times-higher probability of developing IOP elevation. Thyroglobulin (Tg) has been proposed to play a role in GO [ 34 , 35 , 36 ]. Polymorphisms in Tg, along with a combination of iodine and the enzymatic activity of thyroid peroxidase required for thyroid hormone synthesis, may unintentionally trigger an autoimmune response in the thyroid [ 36 , 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thyroglobulin (Tg) has been proposed to play a role in GO [ 34 , 35 , 36 ]. Polymorphisms in Tg, along with a combination of iodine and the enzymatic activity of thyroid peroxidase required for thyroid hormone synthesis, may unintentionally trigger an autoimmune response in the thyroid [ 36 , 37 , 38 ]. The involvement of Anti-TG in GO pathogenesis and their role as risk factor for IOP remains to be elucidated.…”
Section: Discussionmentioning
confidence: 99%